#TITLE_ALTERNATIVE# - SUTOPO (NIM: 33407001) ; Pembimbing Prof. Dr. Ir. Senator Nur Bahagia, WAHYUDI
Staple food which is produced from agro-industry, for example sugar has a salient supply disparity during the harvest season and planting season. This situation causes scarcity and price fluctuation. Moreover, it will bring disadvantages to the stakeholders such as producer, wholesaler, and consumer. A case study about the sugar distribution in Indonesia has found three main reasons which cause those problems. First, the domestic supply does not increase significantly whereas the demand raises continously. Second, there is a significant disparsity of supply between the harvest season and planting season. Third, the price of commodity in a global market is lower than domestic market, so it is possible to harm the producer selling price. If the disparity of supply and price fluctuation can not be alleviated, it may initiate a complex food problem and trigger social and political crisis. On the other hand, government has obligation to protect the producer from selling price distortion and to realize the food sustainability for consumer with a reasonable price. This phenomenon could be solved through implementation of market intervention policy. A buffer stocks scheme could be used as an instrument to control the supply to the markets so that the price will be stabilized and the consumption can be ensured. This paper will discuss the problem on how to determine buffer stocks scheme as an instrument in market intervention program for government to keep the price stabilization and staple food availability. There were many models about price stabilization of staple food that had been developed. Based on literature study, there are some conclusions as follow: (i) an optimization method has been applied to determine the buffer stocks level in guaranting the fulfillment of needs consist of quantity and time; (ii) an econometrics method has been implemented to alleviate the price fluctuation by using the quantity and price of buffer stocks; (iii) generally, the intervention programs only consider producer or consumer expectation; (iv) generally, the organization of buffer stocks scheme only consists of procurement and storaging programs. In another words, the previous models disregarded the following aspects: (i) policies that consider the expectation of stakeholders; (ii) management of buffer stocks scheme consists of planning, procuring, storaging, and releasing v the stocks; and (iii) the intervention system facilitates its stakeholders to act proactively as market players. The objectives of this research are to develop the policy options of cheap, efficient, and fair buffer stocks distribution channel to the entire stakeholders in the distribution system and to develop mathematical model as a tool to formulate the market intervention policy by using buffer stocks scheme. This research produced options of distribution channel policy and mathematical model of buffer stocks scheme as a reference to set up market intervention program. The intervention programs consist of direct market intervention (DMI) through market operation and indirect market invervention (IMI) through warehouse receipt system. There are three policies of distribution channel: monopoly, controlled, and free market. The model consists of three models in DMI policy (Model I-a, I-b, and I-c) and three models in IMI policy (Model II-a, II-b, and II-c). Model DMI is a NLP problem that could be solved by using sequential linear programming (SLP) algorithm. Model IMI is a MINLP problem with NP-hard category. The solusion of IMI model is obtained by applying enumeration method and SLP algorithm. Compare to the previous models, the proposed model is valid for general condition of staple food distribution system in terms of: (i) availability of intervention policy, and distribution channels options; (ii) the model output could be used to manage staple food scheme consists of planning, procuring, storaging, and releasing the stocks; and (iii) the IMI facilitates its stakeholders to act proactively as market players. To evaluate the model performance, several numerical examples have been performed by utilizing historical data. The numerical and analitycal analyses shows that the model can be used to determine the stocks level, the limit of producer’s selling price, the limit of consumer’s purchasing price, the amount of import, and to solve the buffer stocks problem within planning period with considering the interest of stakeholders. Based on Model DMI, government intervention has significant effect to reduce the risks for both producer and consumer side. The intervention policy can be utilized to improve the profit for both the producer and the consumer. Therefore, the government budget rises when the price function parameter rises as well. The Model IMI shows that the IMI does not need a capital as high as DMI. The main contribution of this research are: (i) to integrate the econometrics and optimization approaches in determining the buffer stock scheme, (ii) to develop buffer stock model with considering the market intervention policy, and (iii) to develop market intervention model through a govermental-agent (BLUPP) who acts proactively as market player.